2019
DOI: 10.1055/s-0039-1696706
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Cystic Carcinoma of the Skull Base: Response to Radiation Therapy and Outcomes in a Retrospective Case Series

Abstract: Objectives The main purpose of this article is to examine a single-center cohort of patients with nasopharyngeal adenoid cystic carcinoma (ACC) for pathologic features, skull base invasion, overall survival, and disease-free survival, with a focus on response to proton beam radiation therapy. Design, Setting, and Participants Single-center institutional cancer registry was used to retrospectively identify and analyze outcomes for 12 patients treated for ACC of the nasopharynx from 2000 to 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The overall survival rate at 5 years is 75%, while the 10-years survival rate is 20% and the 15-years survival rate is approximately 10%. 5 The overall prognosis depends on a number of variables. Tubular, cribriform, and solid ACC are the three conventional categories, with the solid subtype having the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival rate at 5 years is 75%, while the 10-years survival rate is 20% and the 15-years survival rate is approximately 10%. 5 The overall prognosis depends on a number of variables. Tubular, cribriform, and solid ACC are the three conventional categories, with the solid subtype having the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows a 40% five-year survival rate for tumors invading the skull base, which is slightly lower than other studies which show an approximate 50 to 60% five-year survival. 2 3 6 A study by Ryckman et al examining the NACC in the National Cancer Database (NCDB) over a similar 10-year period showed that treatment was influenced by treating facility subtype and insurance status. The NCDB has an increased overall study population by increased population sample, but does not allow for geographic distribution analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past two to three decades, this has increasingly been disproven and radiation is a mainstay of therapy. 1 2 6 8 9 10 The role of chemotherapy is overall unclear, as studies show conflicting data with regards to overall survival between patients receiving chemotherapy and radiation therapy alone. 3 6 This can be combined with surgical resection in individual cases due to a high rate of locoregional recurrence, but the overall indolent course of the tumor makes it difficult to recommend either radiation or surgery without consideration of the specific circumstances in each patient and the invasiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations